Pengaruh Struktur Kepemilikan terhadap Financial Distress: Studi Empiris Pada Perusahaan BUMN di Indonesia Tahun 2015 – 2019 - Anja Suryadi; Vanica Serly (Universitas Negeri Padang, 2022)
The purpose of this study is to examine the influence of ownership structure to financial distress. The independent of this study are foreign ownership, institutional ownership, and state ownership. The data in this study are annual reports of BUMN companies in Indonesia that listed in Indonesia Stock Exchange (BEI) in 2015-2019. Total samples are 105 companies. This study used purposive sampling as the sampling method and multiple linear regression as the data analysis. The results of this study indicates that the foreign ownership, institutional ownership, and state ownership have no significant influence to likelihood of financial distress.